2022
DOI: 10.1101/2022.03.05.483071
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

ALS-linked KIF5A ΔExon27 mutant causes neuronal toxicity through gain of function

Abstract: Mutations in the human kinesin family member 5A (KIF5A) gene were recently identified as a genetic cause of amyotrophic lateral sclerosis (ALS). Several KIF5A ALS variants cause exon 27 skipping and produce motor proteins with an altered C-terminal tail (referred to as ΔExon27). However, the underlying pathogenic mechanism is still unknown. In this study, we performed a comprehensive analysis of ΔExon27 at the single-molecule, cellular, and organism levels. Our results show that ΔExon27 is prone to form cytopl… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
16
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 46 publications
0
16
0
Order By: Relevance
“…Our data suggest that the ∆exon27 mutation in KIF5A induces toxic aggregates. Furthermore, while we were preparing this manuscript, a preprint supporting the same conclusion was posted on Biorxiv (Pant et al, 2022). The study showed that KIF5A(∆exon27) causes aggregate formation in cultured cells and is toxic when expressed in Drosophila .…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Our data suggest that the ∆exon27 mutation in KIF5A induces toxic aggregates. Furthermore, while we were preparing this manuscript, a preprint supporting the same conclusion was posted on Biorxiv (Pant et al, 2022). The study showed that KIF5A(∆exon27) causes aggregate formation in cultured cells and is toxic when expressed in Drosophila .…”
Section: Discussionmentioning
confidence: 89%
“…Our data suggest that the Δexon27 mutation in KIF5A induces toxic aggregates. Furthermore, while we were preparing this manuscript, a preprint supporting the same conclusion was posted on Biorxiv (Pant et al, 2022).…”
Section: Discussionmentioning
confidence: 92%
“…Our data suggest that the Δexon27 mutation in KIF5A induces toxic aggregates. Furthermore, while we were preparing this manuscript, a preprint supporting the same conclusion was posted on Biorxiv (Pant et al, 2022). The study showed that KIF5A(Δexon27) causes aggregate formation in cultured cells and is toxic when expressed in Drosophila .…”
Section: Discussionmentioning
confidence: 91%
“…Our data suggest Δexon27 mutation in KIF5A induces toxic aggregations. While we are preparing this manuscript, a preprint showing similar results has been posted on Biorxiv (Pant et al, 2022). They show unpurified KIF5A(Δexon27) in cell lysates is more active than wild type KIF5A; however, it remained elusive KIF5A(Δexon27) by itself is hyperactive or KIF5A(Δexon27) is activated by binding with unidentified factors.…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, given that mutations in the tail and motor domain of KIF22 both disrupt chromosome segregation, the tail and motor domain may interact to inactivate the motor. Head-tail autoinhibition is a known regulatory mechanism of other members of the kinesin superfamily (Blasius et al, 2021; Coy, Hancock, Wagenbach, & Howard, 1999; Espeut et al, 2008; Friedman & Vale, 1999; Hammond, Blasius, Soppina, Cai, & Verhey, 2010; Hammond et al, 2009; Imanishi, Endres, Gennerich, & Vale, 2006; Ren et al, 2018; Verhey & Hammond, 2009; Verhey et al, 1998), and disruption of autoinhibition can be a mechanism of disease pathogenesis (Asselin et al, 2020; Bianchi et al, 2016; Blasius et al, 2021; Cheng et al, 2014; Pant et al, 2022; van der Vaart et al, 2013). Mutations in either the tail or motor domain could disrupt this interaction, preventing KIF22 inactivation in anaphase.…”
Section: Discussionmentioning
confidence: 99%